2023
DOI: 10.3390/toxics11070627
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of In Vitro Genotoxicity of Polystyrene Nanoparticles in Human Peripheral Blood Mononuclear Cells

Milda Babonaitė,
Matas Čepulis,
Jūratė Kazlauskaitė
et al.

Abstract: According to the trade association PlasticEurope, global plastics production increased to 390.7 million tons in 2021. Unfortunately, the majority of produced plastics eventually end up as waste in the ocean or on land. Since synthetic plastics are not fully biodegradable, they tend to persist in natural environments and transform into micro- and nanoplastic particles due to fragmentation. The presence of nanoplastics in air, water, and food causes ecotoxicological issues and leads to human exposure. One of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Both the in vivo and in vitro experiments indicate that NPs can penetrate cell membranes and can be internalized into cells, inducing intracellular biological effects. It has been shown that the cellular granularity (measured by flow cytometry side scatter) can be predictive of NP accumulation in cells [ 34 , 35 ]. The PET NPs of different stages of purity were tested for uptake by the CD14+ monocytes of human PBMCs.…”
Section: Resultsmentioning
confidence: 99%
“…Both the in vivo and in vitro experiments indicate that NPs can penetrate cell membranes and can be internalized into cells, inducing intracellular biological effects. It has been shown that the cellular granularity (measured by flow cytometry side scatter) can be predictive of NP accumulation in cells [ 34 , 35 ]. The PET NPs of different stages of purity were tested for uptake by the CD14+ monocytes of human PBMCs.…”
Section: Resultsmentioning
confidence: 99%